2015
DOI: 10.1017/s0021859614001245
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for wheat spike fertility in cultivars and early breeding materials

Abstract: SUMMARYGrain yield in bread wheat is often tightly associated with grain number/m2. In turn, spike fertility (SF), i.e., the quotient between grain number and spike chaff dry weight, accounts for a great proportion of the variation in grain number among cultivars. In order to examine the potential use of SF as a breeding target, (1) variation for the trait was assessed in six datasets combining commercial cultivars under different environmental conditions, (2) trait heritability was estimated in a set of F1 hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 19 publications
6
36
0
1
Order By: Relevance
“…Interestingly, the yield‐related traits not only exhibited large variation across all experiments and locations but also displayed that genetic effect was consistently larger than genotype × environment interaction, resulting in moderate to high heritability levels. These results are in line with those reported by Mirabella et al (2016), indicating that the studied trait can be improved by selection.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the yield‐related traits not only exhibited large variation across all experiments and locations but also displayed that genetic effect was consistently larger than genotype × environment interaction, resulting in moderate to high heritability levels. These results are in line with those reported by Mirabella et al (2016), indicating that the studied trait can be improved by selection.…”
Section: Discussionsupporting
confidence: 93%
“…These differences may have been caused by differences in ploidy level, length of domestication history [20], or constitutive differences in resources allocation [12,13]. Resource constraints that were imposed on both wheat genotypes for six years triggered similar reaction trajectories, but with largely different magnitudes as demonstrated by other studies [16,17]. Of interest to wheat scientists are traits with narrow (e.g., spike fertility index) or wide range (e.g., biomass) of PPs that can be used as indicators of the buffering capacity of a crop under abiotic stress.…”
Section: Inter-and Intraspecific Variation In Ppssupporting
confidence: 51%
“…Sustained grain set mediated by large spike fertility index is paramount in maintaining yield potential under abiotic stress [8,51]; however, higher population density reduces both the number of floret primordia initiated and floret survival [32,64]; agronomically, this leads to the typical reaction of reduced individual spike fertility, as inferred from its PP, PCV, and GCV (Table 2). This reaction was attributed [73] to delayed spike growth that can be caused by a low red-to-far red ratio in the crop canopy [16].…”
Section: Abiotic Stress Treatmentsmentioning
confidence: 99%
“…Some authors reported a high association ( R 2 = 78%) (Abbate, Pontaroli, Lázaro, & Gutheim, 2013), whereas others observed a weaker relationship ( R 2 = 32%) with a clear underestimation of the trait and with a change in the ranking of cultivars (Elía, Savin, & Slafer, 2016). Previous work showed the strong effect of genotype and a relatively low genotype × environment (G × E) interaction on FE (Amado‐Rivera et al., 2019, Terrile, Miralles, & González, 2017) and FEm (González et al., 2011b, Guo, Slafer, & Schnurbusch, 2016; Mirabella et al., 2016), except for heat stress conditions around anthesis (Terrile et al., 2017). Narrow‐sense heritability for FEm has been reported to be high (Alonso et al., 2018) but it has not been reported for FE yet.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high correlation between GN and FE in cultivars released during the 1990s (Abbate et al., 1998) and after the 2000s (González, Terrile, & Falcón, 2011b), FE was proposed as a trait for improving GN. As the SDWa is complex to measure when the number of plots is large or in early generations, the nongrain spike dry weight at maturity (or chaff) is used as a surrogate for this (e.g., Alonso, Panelo, Mirabella, & Pontaroli, 2018; González et al., 2011b; Martino et al., 2015; Mirabella, Abbate, Ramirez, & Pontaroli, 2016; Stapper & Fischer, 1990). Therefore, FE is often calculated at maturity as the number of grains produced per unit of chaff, referred to in the present work as FEm, following Fischer and Rebetzke (2018).…”
Section: Introductionmentioning
confidence: 99%